(untitled) (Conferencea, 2022)
In this article, we summarize the shift theorem for matrix argument functions. Search for a specific image of the original in the operational account сoncentration image from theorems called shift theorems for table is used. In particular, the shift theorem is generalized for matrix argument functions.